The role of anti-nucleosome antibodies in systemic lupus erythematosus. Results of a study of patients with systemic lupus erythematosus and other connective tissue diseases - V. Tigano; M. Patafi; L. Giannetto; D. Bonanno; A. Barrile; P. Quattrocchi; B. Ferlazzo (PAGEPress Publications, 2011)
Objective: The aim of our study was to investigate the prevalence and the disease specificity of anti-nucleosome antibodies in systemic lupus erythematosus and their association with disease activity and renal involvement. Methods: Anti-nucleosome antibodies were measured by ELISA in the sera of patients with systemic lupus erythematosus (SLE) (47), rheumatoid arthritis (RA) (22), mixed connective tissue disease (MCTD) (19), systemic sclerosis (SSc) (11) and Siögren's syndrome (SS) (10). Anti-dsDNA antibodies were measured by IIF on Chritidia luciliae. In the patients with SLE serum levels of C3 and C4 complement components were also measured. Sera of 22 healthy individuals were assayed as controls. SLE activity was evaluated by the ECLAM score. Results: Anti-nucleosome antibodies were found in 40 patients with SLE (85.1%), in 10 with RA (45.4%), in 8 with MCTD (42.1%), in 4 with SSc (36.3%), in 1 with SS (10%) and in none of the healthy controls. Anti-dsDNA antibodies were found in 23 patients with SLE and were absent in the patients with other CTD and in controls. All the patients with SLE and renal involvement were positive both for anti-dsDNA antibodies and anti-nucleosome antibodies. No significant correlation was observed between anti-nucleosome antibodies and disease activity and renal involvement. Conclusion: Anti-nucleosome antibodies are present in a high percentage of the patients with SLE but they don't seem to be specific markers of the desease. Our data don't support a clear correlation between anti-nucleosome antibodies and disease activity and renal involvement.